2015
DOI: 10.3171/2014.11.jns14315
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical anatomy of the central lobe

Abstract: T he central lobe, composed of the pre-and postcentral gyri and the paracentral lobule is one of the most eloquent areas of the brain, and it corresponds to the sensorimotor cortex. This morphological unit, together with the functional interaction between motricity and sensitivity, justifies the characterization of these gyri as a single lobe. 45There have been several studies of gyral and sulcal anatomy, craniometrics, and vascular features that included this area. 1,4,10,11,17,19,[21][22][23][24]28,36,[39][4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 56 publications
0
30
0
1
Order By: Relevance
“…Sarmento et al [18] stated that the distance between the coronal suture and the central sulcus ranged from 5 to 6.6 cm, in accordance to measurements of Gusmão et al [11] and Ribas et al [12] in the adult. Further, Frigeri et al [19] reported that the precentral gyrus and central sulcus are closest at a point near where the superior temporal line crossed the coronal suture. Further, at this point all the branches of the middle meningeal artery ran posterior to the coronal suture.…”
Section: Discussionmentioning
confidence: 99%
“…Sarmento et al [18] stated that the distance between the coronal suture and the central sulcus ranged from 5 to 6.6 cm, in accordance to measurements of Gusmão et al [11] and Ribas et al [12] in the adult. Further, Frigeri et al [19] reported that the precentral gyrus and central sulcus are closest at a point near where the superior temporal line crossed the coronal suture. Further, at this point all the branches of the middle meningeal artery ran posterior to the coronal suture.…”
Section: Discussionmentioning
confidence: 99%
“…Some highly important cortical regions, such as the central lobe and Broca's area, should be avoided . The precentral gyrus, the site of the primary motor cortex, is also to be avoided . In planning for a target near the fornix, most straight paths started from the precentral gyrus, while feasible curved paths provided entry points in the superior and medial frontal gyrus.…”
Section: Discussionmentioning
confidence: 99%
“…27 The precentral gyrus, the site of the primary motor cortex, is also to be avoided. 28 In planning for a target near the fornix, most straight paths started from the precentral gyrus, while feasible curved paths provided entry points in the superior and medial frontal gyrus. Thus, most straight paths for targeting the fornix are rejected, making our approach of interest for providing safe paths to this region.…”
Section: Discussionmentioning
confidence: 99%
“…The many variations of the sylvian veins consist of superficial and deep sylvian veins, which are three-dimensionally anastomosed with the tributaries from the frontal, temporal, parietal lobes, and the insula. [ 2 6 ] The superficial sylvian vein (SSV) is located on the surface of the sylvian fissure, which is like an entrance into the deep brain area. The sacrifice of the tributaries when entering SSV may potentially cause a catastrophic venous infarction.…”
Section: Introductionmentioning
confidence: 99%